The Modification Effect of Influenza Vaccine on Prognostic Indicators for Cardiovascular Events after Acute Coronary Syndrome: Observations from an Influenza Vaccination Trial - Sribhutorn A. (2017)
© 2016 Apirak Sribhutorn et al. Introduction. The prognosis of acute coronary syndrome (ACS) patients has been improved with several treatments such as antithrombotics, beta-blockers, and angiotensin-converting enzyme inhibitors (ACEI) as well as coronary revascularization. Influenza vaccination has been shown to reduce adverse outcomes in ACS, but no information exists regarding the interaction of other treatments. Methods. This study included 439 ACS patients from Phrommintikul et al. A single dose of inactivated influenza vaccine was given by intramuscular injection in the vaccination group. The cardiovascular outcomes were described as major cardiovascular events (MACEs) which included mortality, hospitalization due to ACS, and hospitalization due to heart failure (HF). The stratified and multivariable Cox's regression analysis was performed. Results. The stratified Cox's analysis by influenza vaccination for each cardiovascular outcome and discrimination of hazard ratios showed that beta-blockers had an interaction with influenza vaccination. M oreover, the multivariable hazard ratios disclosed that influenza vaccine is associated with a significant reduction of hospitalization due to HF in patients who received beta-blockers (HR = 0.05, 95% CI = 0.004-0.71, P = 0.027), after being adjusted for prognostic indicators (sex, dyslipidemia, serum creatinine, and left ventricular ejection fraction). Conclusions. The influenza vaccine was shown to significantly modify the effect of beta-blockers in ACS patients and to reduce the hospitalization due to HF. However, further study of a larger population and benefits to HF patients should be investigated.